ANALISIS FUNDAMENTAL UNTUK MENILAI KEWAJARAN HARGA SAHAM DENGAN MENGGUNAKAN DIVIDEND DISCOUNT MODEL DAN PRICE EARNING RATIO - Fatma Shabrina (2022)
The background of this research is an interest in one of the sectors which, if seen, had extraordinary developments at the end of the PSBB determination, namely the primary consumer goods sector. The type of research is descriptive quantitative with the main focus, namely fundamental analysis using Constant DDM and PER approaches to assess the fairness of stock prices. The aim is to find out and analyze the differences in the fair value of the stock price being undervalued or overvalued using DDM and PER. The population used in this study are consumer goods sector companies that have been listed on the Indonesia Stock Exchange with the observation year 2016-2020, while the sample selection technique uses purposive sampling so that 13 companies as research samples. This study uses SPSS version 25 to test normality and Independent Sample t-Test and Microsoft Excel 2019. The conclusions of this study are 1) The majority of companies as undervalued, 2) The results of the calculation of the fair value of stock prices on issuers of the primary consumer goods sector using either constant DDM or PER do not show significant differences.